The Rotterdam Foot Classification: A Classification System for Medial Polydactyly of the Foot. (3rd August 2016) - Burger, Elise B.; Hovius, Steven E.R.; Burger, Bart J.; van Nieuwenhoven, Christianne A.
Abstract : Background: Polydactyly at the medial side of the foot ("medial polydactyly" of the foot) is a rare and diverse congenital anomaly. In order to plan and evaluate surgical treatment, the classification of medial polydactyly is useful. The aim of our study was to develop a reliable and valid classification system for medial polydactyly of the foot that is more useful than previous systems for preoperative evaluation and surgical planning. Methods: A review of the literature and the clinical experience of a single experienced surgeon were used to determine classification categories. We identified all patients with medial polydactyly who had preoperative radiographs and clinical photographs and were treated at our hospital between 1993 and 2014. All affected feet were assessed according to our proposed classification system, the Rotterdam foot classification. The intrarater and interrater reliability among 5 observers who evaluated 30 feet were assessed with use of the Cohen kappa (κ) statistic. Results: We developed a classification system that describes duplication type, syndactyly, the presence of a hypoplastic ray, and deviation of the hallux. Seventy-three feet were classified according to the system. Seven duplication types were distinguished. Complete metatarsal duplication was most frequently seen (in 29%). Twelve feet showed a broad hallux without external expression of duplication. Syndactyly between medial and lateral (duplicate) halluces was present in 30 feet; between the lateral hallux and second toe, in 13 feet; and between both duplicated halluces and the lateral hallux and second toe, in 21 feet. A hypoplastic ray was seen in 75% of the feet. Intrarater agreement for duplication, hypoplastic rays, syndactyly, and deviation were, respectively, κ = 0.79, 0.75, 0.59, and 0.78. Interrater agreement for duplication, hypoplastic rays, syndactyly, and deviation were, respectively, κ = 0.72, 0.54, 0.48, and 0.64. Conclusions: The proposed classification system contains 4 categories of anatomic features of the foot. Classification of all categories shows moderate to good reliability. Use of the Rotterdam classification in evaluating medial polydactyly improves type-specific description, which may, in the future, enhance the evaluation of surgical treatment. Clinical Relevance: The Rotterdam foot classification system is a reliable and easy-to-use system that we believe will improve communication between clinicians and researchers and facilitate the evaluation of treatment results in medial polydactyly of the foot.